Haiti and the Commonwealth Caribbean : different roads, same destination. - Henry, Andre-Vincent (1992)
Describes the perception of Haiti by English-speaking Caribbean people as one of 'strangeness'. Contends that Haiti, as the first black independent state in the Western Hemisphere, should form a natural focus for scholarly and other investigation. Points out that in many respects, the Commonwealth Caribbean can find itself mirrored in Haiti.